Anti-Hyperlipidemic Effect of Zinc complex of Betulinic acid in High Fat Diet- Induced Hyperlipidemia - Tayyab, Mehwish; Jehangir, Adnan; Ayub, Farhana; Ijaz, Nimra; Ahmed`, Sameer; Munir, Attiya (Journal of Rawalpindi Medical College, 2023)
Background: Hyperlipidemia is considered a modifiable risk factor for cardiovascular disease and atherosclerosis. Drugs of first choice, Statins, despite being well tolerable, are accompanied by many adverse effects. To tackle the shortcomings of standard drugs, there is dire demand to make an agent which equates to a better response. This study evaluated the anti-hyperlipidemic and comparative effects of Zinc complex of Betulinic acid (Zn+BA) with simvastatin (SIM), on high-fat diet-induced hyperlipidemia in rats, and the safety profile of the two treatments was also assessed. Methodology: Hyperlipidemia was induced by giving a high-fat diet. BA +Zn 10 mg/kg and SIM 20 mg/kg were given orally for four weeks. On the final day terminal sampling was done and serum lipid profile (TG, TC, LDL, HDL) and hepatic enzymes (ALT) for assessing hepatotoxicity were estimated. Results: Our results showed that BA+Zn significantly increased HDL levels and significantly reduced serum TC, TG, and LDL (p<0.001) as compared to Simvastatin. Correspondingly serum ALT levels also showed significant reduction (p<0.001) in comparison with Simvastatin. Conclusion: Our study suggests that BA+Zn effectively attenuates high-fat diet-induced hyperlipidemia while preserving hepatic function and could serve as a better alternative to simvastatin in treating hyperlipidemia.